The relationship between human resource management practices and turnover intention in a manufacturing company: The mediating effect of employee engagement - Lai, Say Wei (2013)
Employee turnover is crucial to be received considerable attention by organizations since it has proven to be one of the most costly that could diminish an organization's morale and budget. The purpose of this study was to examine the mediating effect of employee engagement between Human Resource Management (HRM) practices (training and development, career development, rewards and recognition and performance appraisal and achievements) and turnover intention. Besides that, it also investigated the relationship between HRM practices and turnover intention as well as the relationships of employee engagement and turnover intentions. There has existed a lack of information about the relationship between HRM practices, employee engagement and turnover intention and the mediating effect of engagement among these variables. A total of 180 survey questionnaires were distributed to the respondents in company X and 150 sets of questionnaires returned were used for the further analyses. The data analyzed by "Statistical Package for Social Science" (SPSS Window) Version 16.0. The study utilized the reliability analysis, descriptive statistics, independent-samples T-test, One-way ANOVA, Pearson Correlation and multiple regression analysis to examine relationships between human resource management practices, employee engagement and turnover intention. From the findings, the Cronbach's Alpha values for dependent variable, independent variables (HRM practices) and mediating variable (employee engagement) were considered acceptable. Independent-samples T-test revealed that there is no significant difference in turnover intention reported by male and female respondents. Besides that, One-way ANOVA indicated that turnover intentions differ with the aged groups and also academic qualification. The findings of the study found that the relationship of turnover intention with both of rewards and recognition and performance appraisal and achievements generally support the presented hypothesis as well as the mediation effect of employee engagement on those relationships. Some suggestions has been recommended for practitioners and academicians and future research needs to include more diversified samples and broaden the scope of current research by examining other human resource practices dimensions and including other types of industry